Implementation of Pharmaceutical Care Standard in Jambi City's Pharmacies - Mulyagustina Mulyagustina; Chairun Wiedyaningsih; Susi Ari Kristina (Faculty of Pharmacy, Universitas Gadjah Mada)
In the last five years, the pressure to implement pharmaceutical care focuses on the patient getting stronger. The current standard of pharmacy care at a pharmacy established by regulation of health minister number 73/2016, as a guideline for pharmacists and pharmacy technicians in organizing pharmaceutical care. This research was conducted in the city of Jambi in order to determine implementation of pharmaceutical care standard at pharmacy, to identify the supporting factors and inhibiting factors in implementing pharmaceutical care in the Jambi city’s pharmacy. This study is an observational descriptive study, conducted with a survey phase, followed by a phase of observation and in-depth interviews phase. Total respondents who conducted a survey of 105 pharmacist from 143 pharmacies. Then performed an observation using a checklist sheet at 20 pharmacies and in-depth interviews on 17 pharmacists. The questionnaire survey used convenience sampling technique and sampling techniques for observation and in-depth interviews with maximum variation sampling. Methods of data analysis was done descriptively to see the implementation of pharmaceutical care standard. Qualitative data were presented descriptively to identify supporting and barriers factors. Results of the research are based on a survey, in managing the pharmaceutical, medical supplies and consumable medical materials carried out by pharmacist assisted pharmacy technicians, but its implementation in the field is mostly done by the pharmacy technicians under the responsibility of the pharmacist. Clinical pharmacy services running on prescription services, drug information services and partly on the counseling. Home pharmacy care, monitoring drug therapy and monitoring of drug side effects and clinical documentation has not been done. Based on interviews unknown, factors supporting the implementation of the standard is support pharmacy technicians personnel, support of owner pharmacy, the presence of a pharmacist with a regular schedule of practices, the use of information systems technology and motivation of pharmacist. Whereas the barriers factor are factors in patients where there is doubt the patient to the pharmacist and staff, the limited presence of the pharmacist, the shortage of skills,and there is no space of counseling services and the limited number of pharmaceutical human resources.